PERAN DISTRIBUSI ZAKAT PRODUKTIF TERHADAP PENINGKATAN KESEJAHTERAAN MUSTAHIK KAMPUNG ZAKAT TERPADU JEMBER - Afifah, Fadhilah Zahrotul; Permana, Muhammad Yogi Galih (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Productive zakat aims to support mustahik’s business so that they can fulfill their needs consistently and not spent on consumption, so that mustahik can change their status from mustahik to muzakki. This research was prepared to find out how the distribution of productive zakat in Kampung Zakat Terpadu Jember and its implication to the improvement of mustahik welfare of mustahik. The methodology used is descriptive qualitative field study and used the methods of interview, documentation, and observation to accumulate data. his research is different from previous research which shows that the distribution of productive zakat has a positive and significant relationship with the improvement of mustahik welfare which includesskills training, micro business funding, or capital assistance to start a business. As for yhis research, it shows that the distribution of productive zakat does not have a significant relationship with improving the welfare of mustahik’s welfare. Based on the research that has been conducted, researchers can conclude that distribution carried out by BAZNAS and zakat management institutions complies with the applicable procedures and the provisions pertaining to zakat administration found in Law Number 23 of 2011. In Kampung Zakat Terpadu Jember, productive zakat plays a crucial role in generating employment opportunities and enhancing the welfare and standard of living of the local community mustahik, thus creating new muzakki and transforming someone into a muktafi. The researcher categorizes the benefits received by the mustahik into three groups: (1) not feeling any significant benefits and not experiencing economic changes. (2) experiencing short-term benefits and not experiencing economic changes. (3) experiencing long-term benefits and experiencing economic improvement. Keywords: productive zakat, zakat village, welfare.